First order differential equations System that describes T cells and Chronic Myelogenous Leukemia interaction - Rodas Cabanillas, José Luis (2016)
In this research was studied the interaction from a mathematical point of the human immune system T cells: naive and voters, with chronic myelogenous leukemia cells. (CML). This interaction was known through a system of nonlinear ordinary differential equations that describe the instantaneous variation of these three populations of cells. Emphasis is placed on finding solutions of analytical balance and numerically using the matlab software, and study their stability, for this purpose it has been used data obtained from similar studies and data from diseases whose pathology involves T cells as a defense mechanism, such is the case of the human immune deficiency virus. 12 parameters are examined and it has concluded that for stability, two parameters are important, the growth rate and the death rate of chronic myelogenous leukemica cells.